The impact of low Al-content waveguides on power and efficiency of 9xx nm diode lasers between 200 and 300 K. (3rd December 2015) - Frevert, C; Crump, P; Bugge, F; Knigge, S; Erbert, G
Abstract: We present results on investigations of 9xx nm, GaAs-based diode lasers with 100 μ m wide, 4 mm long stripes operating at temperatures between 200 and 300 K. As temperatures are reduced to 218 K, efficiency and power are improved. We analyze the characteristic parameters and subsequently mitigate the limiting factors by altering the vertical epitaxial design, seeking to further increase the optical output power and efficiency. The temperature dependence of internal parameters is obtained from length-dependent measurements, showing that the improved performance is due to an increased differential internal efficiency. Series resistance is confirmed as the main remaining limit to higher efficiency at high power. We show that the series resistance can be reduced by lowering the aluminum content in the Al x Ga1− x As waveguide which increases the carrier mobility. Although poor optical performance is seen at room temperature in low Al-content structures due to carrier leakage, at 218 K this is suppressed and is accompanied by significantly reduced series resistance. However, at high powers we observe further (non-thermal) power saturation in low Al-content structures even at 208 K, which limits the efficiency gain at high powers. Analysis of the series resistance of laser structures with different waveguide compositions at temperatures between 208 and 298 K reveals that series resistance is a function of the barrier height around the quantum well. This is taken as first evidence for carrier transport being a significant limit to electrical resistance. Finally, structures with an optimized Al-content are shown to maintain conversion efficiency >65% to output powers of 20 W, substantially higher than previously reported at 300 K (∼55% at 20 W).